Gedenkboek van de Rijksuniversiteit te Gent na een kwarteeuw vervlaamsing (1930-31 - 1955-56). - Luykx, Theo (Gent : RUG, 1957)
Bibliotheek Camille Huysmans
Nederlands
Monografie
Keywords: Universiteit Gent (UG).; Dhondt, Jan